POLITICAL CONNECTION AND TAX AVOIDANCE: EVIDENCE FROM TWO-TIER BOARD SYSTEM IN INDONESIA - Diningrum, Nola; Kurniawati, Estetika (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
Tax avoidance remains an ongoing issue on a global scale, especially in developing countries. This study aimed to examine the relationship between political connections on the board of commissioners and directors and tax avoidance. This study analyzed manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022, selected through a purposive sampling method to produce 289 observations. To enhance the analysis, this study used BTD and CETR to measure tax avoidance. Overall, the results showed that political connections of the board of commissioners had a negative influence on tax avoidance. However, the political connections of the directors did not influence tax avoidance. The board of commissioners can prevent actions that could damage the corporation's reputation by monitoring and advising the directors on tax strategies. This study contributes to the upper echelon theory by demonstrating that the political experience of the board of commissioners suppresses tax avoidance.